Effects of Feeding High Tryptophan GM-Rice on Growth Performance of Chickens - Takada, Ryozo; Otsuka, Makoto (International Journal of Poultry Science, 2007)
Recently, high tryptophan genetically modified (GM)-rice has been newly developed and its tryptophan content was 50% higher than conventional rice. The goal of this experiment was to clarify the nutritive value of high tryptophan GM-rice on chicken growth performance. Experimental treatments were the following, 1) NB (control) group; brown rice (Nihonbare) based low protein diet in which all the deficient essential amino acids except tryptophan were added to meet the nutritional requirement, 2) NB+Trp group; control diet+crystalline tryptophan, 3) HW-1 (GM Trp) group; GM-brown rice (high tryptophan) based low protein diet in which all the deficient essential amino acids except tryptophan were added. Twenty one birds of Boris brown male chickens (7 days of age and 80±2 g of initial body weight) were used. They were assigned to three experimental groups, each of which contained 7 birds. The birds were individually housed in electrically heated battery cages maintained in temperature constant (24 degrees) room. They had free access to experimental diet and water during an experimental period of three weeks. Body weight gain in NB+Trp group and HW-1 group were significantly higher than that in control group. Similarly, higher feed intake in NB+Trp group and HW-1 group compared with control group were observed. Feed efficiency (gain/feed) in HW-1 group was significantly higher than in control group. These results show that the nutritional value of high tryptophan GM-Rice is similar to that of non-GM rice supplemented with crystalline tryptophan.